Kepemimpinan Tradisional dalam UU Simbur Cahaya di Desa Pajar Bulan Tanjung Batu Ogan Ilir - Fitria, Bela; Otoman, Otoman (Ampera: A Research Journal on Politics and Islamic Civilization, 2021)
ABSTRACTThis paper examines Traditional Leadership in the Simbur Cahaya Law (Case Study: Pajar Bulan Village, Tanjung Batu District, Ogan Ilir Regency). The background of the research problem because leadership is an essential thing which actually needs to be studied in various fields of knowledge. This study seeks to portray the history and forms of traditional leadership that have been applied in Pajar Bulan Village and the relevance of the Simbur Cahaya Law with current leadership. This type of research uses a qualitative research type with various procedures and stages that produce descriptive data. The data sources obtained are primary data and secondary data. Methods of data collection are carried out through interviews, observation and documentation. The data analysis technique used was data reduction, data presentation and conclusion drawing. The conceptual and theoretical framework that the writer uses, namely the concept of leadership and the theory of authority put forward by Max Weber. The results showed that the leadership that had been applied in Pajar Bulan Village before the current leadership was traditional leadership that was based on the Simbur Cahaya Law. The traditional leadership that has been applied in Pajar Bulan Village is known as krio leadership. In which the selection of a krio was held by means of deliberation and consensus held by community leaders in Pajar Bulan Village. Furthermore, after the election of a krio, it was immediately announced to all levels of society in Pajar Bulan Village and the community immediately agreed to it. In this regard, the traditional leadership system has no influence in the current government leadership in Pajar Bulan Village. Furthermore, the rules of the Simbur Cahaya Law that are still used and have become a tradition in Pajar Bulan Village are some of the rules contained in Chapter 1 (one) of the Simbur Cahaya Law which regulates single, girl and marriage. As for the Simbur Cahaya Law, it is not a legislative product as its name suggests. Which, if viewed in terms of the relevance of the Simbur Cahaya Law to the current leadership of the village head, is the local customary law (pearaturan) that has become a tradition or in other words the customary law regulations from the Simbur Cahaya Law are used as guidelines and pointers. Keywords: leadership, traditional, simbur cahaya law